Figurative Language Used By Gayle Forman In "If I Stay" Novel - Sriwulandari, Novi; Yaqin, M.Ainul; Dewi, Risma Kartika; Bayuandra, Dennis (Procedia of Social Sciences and Humanities, 2022)
This study investigated the figurative languages used in a novel written by Gayle Forman entitled "If I Stay Novel". The researchers analyzed six figurative languages; Metonymy, Symbolic, Euphemistic, Litotes, Onomatopoeia, and Idiom. This study is descriptive qualitative. The data were in the form of sentences gained by doing several steps. The first step was reading the novel. The second was to identify and find the sentences that belong to Metonymy, Symbolic, Euphemistic, Litotes, Onomatopoeia, and Idiom. The next step was underlining the phrase or words that belong to figurative languages. After that, in analyzing the data, the researchers classified the sentences into six figurative languages, analyzed sentences, and interpreted them. In conclusion, the figurative languages in this novel contain 42% Metonymy, 5% Symbolic, 8% Euphemistic, 3% Litotes, 13% Onomatopoeia, and 29% Idiom.